Validation of the World Health Organization's Abbreviated Quality of Life Scale on a Sample of Children with Cancer at Rambam Hospital in Haifa, Palestinian Territories - Otallah, Adnan Mahmoud (Journal of Educational and Psychological Sciences, 2025)
The study aims to validate the World Health Organization's abbreviated Quality of Life scale (WHOQOL-BREF) on a sample of children with cancer at Rambam Hospital in the Palestinian territories. The scale's validity was assessed through content validity and construct validity. The initial version of the scale was reviewed by five experts, with an 80% agreement criterion for item modification. Based on their feedback, certain items were revised, resulting in a final scale of 30 items.Construct validity was examined by calculating the correlation coefficients between each item and the total score for its domain and the overall scale using Pearson correlation. The results indicated that all items showed positive correlations with their respective domains and the overall scale, with correlation values ranging from -0.292 to 0.838, demonstrating strong and moderate statistical significance at the 0.01 and 0.05 levels, respectively, which indicates good construct validity for the scale.Reliability of the scale was assessed using Cronbach's alpha, split-half method, and the Spearman-Brown formula. The reliability coefficients ranged from 0.326 to 0.821 for Cronbach's alpha, from -0.562 to 0.774 for the split-half method, and from 0.074 to 0.860 for the Spearman-Brown formula. The negative values observed in the split-half method suggest the need for revising certain items. The high values overall indicate that the scale demonstrates high validity and reliability coefficients. No significant differences were found in the overall scale scores among the children. Based on the findings, the researcher proposed several recommendations and suggestions.
Keywords: Scale validation; quality of life; validity; reliability; Pediatric cancer